Extracted tissue‐specific atelocollagens have distinctive textural properties. Issue 5 (26th September 2022) - Nakamura, Sayaka; Hoshi, Hiroko; Wakabayashi, Kaito; Seki, Manami; Watanabe, Makoto; Watanabe, Momoka; Inaba, Hiroki; Ushijima, Natsumi; Akasaka, Tsukasa
Abstract: Food texture is a very important factor for elderly persons, children, and patients who have difficulty swallowing. Collagen and its hydrolysis product, gelatin, are used as ingredients in foods, dietary supplements, and medical materials. In this study, we extracted atelocollagen from nonedible porcine tissues, including ear, nose, and skin, and analyzed the biophysical properties of each tissue. Extracted whole auricle collagen (AEC) showed superior springiness, while only the skin region of auricle collagen (ASC) showed superior hardness, springiness, and brittleness. Body skin collagen showed high hardness but low springiness. In a shear stress test, ASC gels showed high shear strength, and their strains coincided with hardness in a textural examination, while nose and AEC showed low maximum strains. In viscosity, the auricular collagens showed higher viscosity regardless of the region of the ear. Fibril formation in collagen from each tissue and organ varied a great deal in width and morphology. We found that the same type of collagen had a unique texture and viscosity under physiological conditions depending on the tissue or organ of extraction. The results show that the collagen extracted from each organ has a unique texture and unique possibilities to serve as an ingredient in food or supplements. Abstract : Atelocollagen extracted from different tissues had unique texture properties.